Keefektifan Model Think Pair Share (TPS) dalam Pembelajaran Apresiasi Cerita Pendek - Angraini, Nani; Hastuti, Hastuti; Liana, Eva (LPPM STKIP PGRI Bandar Lampung, 2024)
The purpose of this study is to describe reading ability and describe cooperative learning models in reading short stories. The type of this research is quantitative research, namely experiments. In collecting data used include tests, observations and interviews. The sample in this study were second semester students of STKIP PGRI Bandar Lampung. Data analysis techniques used were normality tests and homogeneity tests. The results of this study indicate that the ability to read short stories after using the think pair share model is categorized as very good. This can be seen through the percentage of students who succeeded, which was 96.66%.